Systemic oxidative stress is associated with lower aerobic capacity and impaired skeletal muscle energy metabolism in heart failure patients - Takashi Yokota (Nature Portfolio, 2021)
Abstract Oxidative stress plays a role in the progression of chronic heart failure (CHF). We investigated whether systemic oxidative stress is linked to exercise intolerance and skeletal muscle abnormalities in patients with CHF. We recruited 30 males: 17 CHF patients, 13 healthy controls. All participants underwent blood testing, cardiopulmonary exercise testing, and magnetic resonance spectroscopy (MRS). The serum thiobarbituric acid reactive substances (TBARS; lipid peroxides) were significantly higher (5.1 ± 1.1 vs. 3.4 ± 0.7 μmol/L, p < 0.01) and the serum activities of superoxide dismutase (SOD), an antioxidant, were significantly lower (9.2 ± 7.1 vs. 29.4 ± 9.7 units/L, p < 0.01) in the CHF cohort versus the controls. The oxygen uptake (VO2) at both peak exercise and anaerobic threshold was significantly depressed in the CHF patients; the parameters of aerobic capacity were inversely correlated with serum TBARS and positively correlated with serum SOD activity. The phosphocreatine loss during plantar-flexion exercise and intramyocellular lipid content in the participants' leg muscle measured by 31phosphorus- and 1proton-MRS, respectively, were significantly elevated in the CHF patients, indicating abnormal intramuscular energy metabolism. Notably, the skeletal muscle abnormalities were related to the enhanced systemic oxidative stress. Our analyses revealed that systemic oxidative stress is related to lowered whole-body aerobic capacity and skeletal muscle dysfunction in CHF patients.